Petrophysical Analysis to Map Geological Significance of Sawan Gas Field, Sindh, Pakistan - Khan, M. J.; Shakir, U.; Mahmood, M. F.; Hussain, R.; Bukhari, S.R.F.; Khaskheli, M. (The Nucleus, 2021)
[1] PPL official e-report, Sawan Gas Field. www.ppl.com.pk/content/sawan-gas-field-overview, 2018. [2] M.J. Khan, M. Umar, M. Khan and A. Das, â€œ2D Seismic Interpretation to Understand the Structural Geometry of Cretaceous Sand Packages, Jabo Field, Pakistanâ€, The Nucleus, vol. 56, pp 78-85, 2019. [3] H.M. Anwer, A.M. Tiago, A. Ali and A. Zubair, â€œEffects of sand shale anisotropy on amplitude variation with angle (AVA) modelling: the sawan gas filed (Pakistan) as a key study for south Asiaâ€™s sedimentary basinsâ€, J. Asian Earth Sci, vol. 147, pp. 516-531, 2017. [4] T.S. Abbas, K. Mirza and J.S. Arif. â€œLower Goru Formation-3D Modeling and Petrophysical Interpretation of Sawan Gas Field, Lower Indus Basin, Pakistanâ€, The Nucleus, vol. 52, pp.138-145, 2015. [5] S.M. Siyar, M. Waqas, S. Mehmood, A. Jan, M. Awais and F. Islam, â€œPetrophysical characteristics of Lower Goru Formation (Cretaceous) in Sawan gas field, Central Indus basin, Pakistanâ€. J. Biodiv. Envir. Sci., vol. 10, pp. 260-266, 2017. [6] N. Ahmad and M.R. Khan, â€œEvaluation of a Distinct Sub-Play for Enhanced Exploration in an Emerging Petroleum Province, Bannu-Kohat Sub-Basin, Pakistanâ€. AAPG Int. Conf. and Ex., Milan, Italy, October 23-26, 2011. [7] M.J. Khan, M. Ali and M. Khan, â€œGamma ray-based facies modelling of lower Goru formation: a case study in Hakeem Daho well lower Indus basin Pakistanâ€, Bahria Univ. Res. J. Earth Sci., vol. 2, pp. 40-45, 2017. [8] M.O. Baig, N.B. Harris, H. Ahmed and M.O.A. Baig, â€œControls on reservoir diagenesis in the Lower Goru Sandstone Formation, Lower Indus basin, Pakistanâ€, J. Pet. Geol., vol. 39, pp. 29â€“47, 2016. [9] A. Berger, S. Gier and P. Kroi, â€œPorosity-preserving chlorite cements in shallow marine volcanoclastic sandstones; evidence of the Sawan gas field Pakistanâ€. AAPG Bull., vol. 93, pp. 595-615, 2009. [10] N. Ahmed, P. Fink, S. Sturrock, T. Mahmood and M. Ibrahim, â€œSequence stratigraphy as predictive tool in lower Goru fairway, lower and middle Indus platform, Pakistanâ€, Pak. Assoc. Petro. Geoscientist, Annual Tech. Conf., pp. 85-104, 2004. [11] U.B. Nisar, S. Khan, M.R. Khan, A. Shahzad, M. Farooq and S.A.A. Bukhari, â€œStructural and reservoir interpretation of Cretaceous lower Goru formation, Sanghar area, Lower Indus basin, Pakistanâ€, J. Himalaya Earth Sci., vol. 49, pp. 41-49, 2016. [12] I.B. Kadri, â€œPetroleum geology of Pakistanâ€, Pakistan Petroleum Limited, Karachi, 1995. [13] T. Azeem, Y.W. Chun, P. Khalid, I.M. Ehsan, F. Rehman and A.A. Naseem, â€œSweetness analysis of Lower Goru sandstone intervals of the Cretaceous age, Sawan gas field, Pakistanâ€, Episodes: J. Int. GeoSci., vol. 41, pp. 235-247, 2018. [14] C.J. Wandrey, B.E Law and H.A. Shah. â€œSembar Goru/Ghazij composite total petroleum system Indus and Sulaiman-Kirthar geologic Provinces Pakistan and Indiaâ€, US Geolog. Survey, USA, 2004. [15] M. Naeem, M.K. Jafri, S.S. Moustafa, N.S. AL-Arifi, S. Asim, F. Khan and N. Ahmed, â€œSeismic and well log driven structural and petro-physical analysis of the Lower Goru Formation in the Lower Indus Basin, Pakistanâ€, Geosci. J., vol. 20, pp. 57â€“75, 2016. [16] A. Nazeer, S.A. Abbasi and S.H. Solangi, â€œSedimentary facies interpretation of Gamma Ray (GR) log as basic well logs in Central and Lower Indus Basin of Pakistanâ€, Geodesy Geodyn. 7, pp. 432-443, 2016. [17] N. Ahmad and S. Chaudhry, â€œKadanwari gas field, Pakistan: a disappointment turns into an attractive development opportunityâ€, Petrol. Geosci., vol.8, pp. 307â€“316, 2002. [18] J.J. Chow, L. Ming-Ching and S. Fuh, â€œGeophysical well log study on the paleoenvironment of the hydrocarbon producing zones in the Erchungchi Formation, Hsinyin, SW Taiwanâ€, Terr. Atmos Ocean Sci., vol. 16, pp. 531-543, 2005. [19] M. Ali, M.J. Khan, M. Ali and S. Iftikhar, â€œPetrophysical Analysis of Well Logs for Reservoir Evaluation: A Case Study of â€˜Kadanwariâ€™ Gas Field, Middle Indus Basin, Pakistanâ€, Arabian J. Geosci. vol. 12, 2019. [20] I.A.K. Jadoon, R.D. Lawrence and R.J. Lillie, â€œSeismic data, geometry, evolution, and shortening in the active Sulaiman Fold-and-Thrust Belt of Pakistan, Southwest of the Himalayasâ€, AAPG Bull., vol. 78, pp. 758â€“774, 1994. [21] S.H. Solangi, A. Nazeer, S.A. Abbasi, L.D. Napar, P.A. Usmani and A.G. Sahito, â€œSedimentology and petrographic study of B-sand of Upper sands of Lower Goru Formation, based well cuttings and wire line logs from wells of southern Sindh monocline, lower Indus basin, Pakistanâ€, Bahria Uni Res. J. Earth Sci. vol. 1, pp 45-54, 2016. [22] G. Asquith and C. Gibson, â€œBasic well log analysis for geologistsâ€, AAPG methods in exploration series, Tulsa, pp. 2l6, 1983. [23] F.J. Lucia, â€œRock-fabric/petrophysical classification of carbonate pore space for reservoir characterizationâ€, AAPG bulletin, vol. 79, pp. 1275-1300, 1995. [24] M.H. Rider, â€œGeologic interpretation of well logsâ€, Whittles Publishing Services, 1999.